Gaya Bahasa Propaganda Penjajahan Zionis Israel terhadap Warga Palestina: Tinjauan Stilistika - Lilimiwirdi, Lilimiwirdi; Fitria, Novi; Tri Putra, Roni; Sukatik, Sukatik (Puitika, 2025)
Gaza war between Israel and Palestine has involved the international community. The news related to the war appears in the mass media in various styles. The media chosen as the sample was Kompas published from 1 October 2023 to 1 August 2024. The method used is the listening method. Listening is not only related to the use of spoken language but also written language. Languages of propaganda used by Israel in fighting against Palestinians are as follows. First, figures of speech based on sentence structure are climax, anticlimax, parallelism, antithesis, and repetition. Second, figures of speech based on the directness or indirectness of meaning include euphemism, pleonasm and tautology, erotesis or rhetorical question, hyperbole, prolepsis or anticipation, chiasmus, assidenton, correction or epanorthosis, figurative language, metaphor, metonymy, allusion, irony, cynicism, and sarcasm. The language of propaganda influences psychology and culture. Its influence on psychology can be seen in the psychology of Palestinian people affected by the war and the psychology of readers reading news that is terrible, sadistic, and full of fear. Then, the effects on culture is the attitude of many consumers who boycott Israeli products; in the security field, the high level of crime and insecurity in the Palestinian territories and surrounding areas; the high number of muallaf (converts) and interest in leading Islam due to the attitude and morals of the Palestinians who are steadfast in facing the war; and high solidarity in helping Palestinians. Moreover, it also influences the language, namely new words, symbol language, and expressions used during the war.